FEATURES AND STATE OF PRESERVATION OF THE GARDEN OF SEHZADE RESIDENCES AT YILDIZ PALACE - Uguryol, Drahsan; Uguryol, Mehmet (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2017)
The Garden of Sehzade Residences is located in Yildiz Technical University Yildiz (Besiktas) Campus situated at the northwestern part of Yildiz Palace. The garden was designed according to the slope of the site, and has authentic elements such as tree branch-shaped parapets, grotto ornaments with cascades, pavements adorned with various bordures, fountains and pools, stairs and pergolas, and a footbridge designed like tree branches. Despite the requirements related to new functions of the buildings surrounding the garden have resulted in modifications in the republican period, the latest form of the garden in Ottoman period is rather preserved as it is being located in the campus; however, the degree of deterioration in authentic architectural elements exposed to environmental factors has increased locally in areas of concentrated use. The Garden of Sehzade Residences and its state of preservation are examined in this paper composed of three sections. Yildiz Palace gardens, which were influenced by English garden design seen in Istanbul in the 19th century, and which the Garden of Sehzade Residences belongs to, were examined in the first section. Design features of the Garden of Sehzade Residences and its present state including its preservation problems are discussed in the second section, which is the main part of the study. The paper is concluded with a general evaluation of the whole study and with suggestions in the third section.
Keywords: Historical Gardens; Garden of Sehzade Residences; Preservation Problems; Yildiz Palace; Art